Computed tomography and magnetic resonance imaging of a rhinosinusitis secondary to a dental abscess in a crested porcupine (Hystrix cristata) - Encinoso, Mario (Slovenian veterinary research, 2023)
A captive crested porcupine (Hystrix cristata) adult male was imaged due to reduced food intake, anorexia, fever, nasal discharge, changes in fecal quantity and size, and respiratory difficulties. Advanced imaging diagnostic techniques such as computed tomography and magnetic resonance imaging were performed to evaluate the animal. These techniques were very helpful to delineate the dental abscess, as well as the extension of the process to other locations such as the nasal cavity and the tympanic bulla. This is the first description of rhinosinusitis secondary to a dental abscess in a crested porcupine.
Keywords: computed tomography; dental abscess; ježevec; Magnetic Resonance Imaging; magnetna resonanca; porcupine; Porcupines; računalniška tomografija; Tomography; zobni absces